1997
DOI: 10.1080/016909697386664
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of Activation of Semantic Information during Spoken Word Recognition

Abstract: We investigated the time course of activation of the mental representatio ns of word meanings in a series of three cross-modal priming experiments. In Experiment 1, we showed a signi cant priming effect for semantically related targets presented at the "isolation point" of the prime word, con rming earlier evidence for the activation of multiple word meanings before the point at which a word can be recognised. The use of non-associated prime-target materials ruled out the possibility that this could be an arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
1
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 41 publications
3
71
1
3
Order By: Relevance
“…But when two types of competitor are copresent one type of information may be weighed more strongly than the other. Categorical/functional knowledge, for instance, is a particularly salient aspect of lexical knowledge (e.g., Moss et al, 1997); it is not difficult to imagine a model in which the strength of the activation of particular features in a given situation translates into the probability of attending towards whatever shares those features.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…But when two types of competitor are copresent one type of information may be weighed more strongly than the other. Categorical/functional knowledge, for instance, is a particularly salient aspect of lexical knowledge (e.g., Moss et al, 1997); it is not difficult to imagine a model in which the strength of the activation of particular features in a given situation translates into the probability of attending towards whatever shares those features.…”
Section: Methodsmentioning
confidence: 99%
“…Pecher, Zeelenberg, and Raaijmakers (1998), however, found perceptual priming only if participants were first given practice in categorizing primes and targets in a perceptual categorization task. Moss, McCormick, and Tyler (1997), using the lexical decision task, found a significant priming effect for functional properties of words early during the duration of the word but priming for perceptual targets (e.g., the colour overlap between aspirin and white) only at the offset of the prime word. Kellenbach, Wijers, and Mulder (2000) obtained robust perceptual priming as indexed by the event-related potential (ERP) N400 component but contrary to Moss et al (1997) observed no effect for the same materials from the ERP study when used in a lexical decision task.…”
Section: Perceptual Priming and Word Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Dell and Reich (1981) found a strong lexical bias in their corpus of errors in spontaneous speech, Garrett (1976) found no such effect and Stemberger (1985) found only a weak effect. In an analysis of the errors in picture naming of fifteen aphasic speakers, Nickels and Howard (1995) found no evidence for lexical bias. A feedback account of the lexical error bias is provided by the DSMSG model.…”
Section: Modeling Spoken Word Productionmentioning
confidence: 99%
“…Evidence for the multiple activation of lexical candidates during word recognition comes from cross-modal semantic priming experiments (e.g., Moss, McCormick, and Tyler 1997;Zwitserlood 1989). For example, Zwitserlood (1989) asked participants to listen to spoken words (e.g., CAPTAIN) or fragments of these words (e.g., CAPT).…”
Section: Modeling Spoken Word Recognitionmentioning
confidence: 99%